Measuring awareness about child abuse and neglect: Validity and reliability of a newly developed tool-child abuse and neglect awareness scale - Hüsniye Altan; Işıl İrem Budakoğlu; Figen Şahin-Dağlı; Resmiye Oral (The Turkish Journal of Pediatrics)
In this study, we aimed at determining child abuse and neglect awareness of medical students attending one of the top medical schools in Turkey. The study group comprised 350 third-year medical students at Gazi University, School of Medicine, Ankara. The items in the scale were prepared by two experienced pediatricians and revised according to feedback received from two pilot studies and experts in this field of study. A 20-item `Child Abuse and Neglect Awareness` scale (CANA-S) was developed by an expert panel. Exploratory and confirmatory factor analyses were performed. We also measured test-retest reliability and internal consistency. Conformity for factor analysis of the scale`s construct validity revealed a Kaiser-Meyer-Olkin sample concordance coefficient of 0.799. For the Bartlett Sphericity test, χ2 value was 1157.750 (p < 0.01). Based on these analyses, the scale explains 44.9% of the total variance and consists of 20 items and 4 subscales. Cronbach`s alpha value and correlation coefficient were 0.768 and r=0.204 (p=0.045), respectively. This scale is a valid and reliable measurement tool for evaluating awareness about child abuse and neglect among the medical students.